2018
DOI: 10.1016/j.arth.2018.03.031
|View full text |Cite
|
Sign up to set email alerts
|

The Safety of Tranexamic Acid in Total Joint Arthroplasty: A Direct Meta-Analysis

Abstract: Although most studies included in our analysis excluded patients with a history of prior thromboembolic events, our findings support the lack of evidence of harm from TXA administration in patients undergoing TJA. Moderate evidence supports the safety of TXA in patients undergoing total knee arthroplasty with an ASA score of 3 or greater. The benefits of using TXA appear to outweigh the potential risks of thromboembolic events even in patients with a higher comorbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
101
0
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(116 citation statements)
references
References 83 publications
5
101
0
10
Order By: Relevance
“…The practice of targeted TXA administration could possibly remain appropriate when the impact of safety is considered. However, although the present study is underpowered to show clinically significant differences in complication rates, it is nonetheless congruent with a growing body of meta‐analyses and database reports, some very recent, that continue to report no evidence of harm with TXA use among TJA patients . Despite the growing body of evidence showing no increased risk of SAEs, we nonetheless suggest ongoing vigilance, particularly for thrombotic events in high‐risk patients.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The practice of targeted TXA administration could possibly remain appropriate when the impact of safety is considered. However, although the present study is underpowered to show clinically significant differences in complication rates, it is nonetheless congruent with a growing body of meta‐analyses and database reports, some very recent, that continue to report no evidence of harm with TXA use among TJA patients . Despite the growing body of evidence showing no increased risk of SAEs, we nonetheless suggest ongoing vigilance, particularly for thrombotic events in high‐risk patients.…”
Section: Discussionsupporting
confidence: 81%
“…The recognition of groups that benefit marginally or not all from TXA may warrant a targeted approach to TXA use, whereas the demonstration that all patients, with and without risk factors, benefit meaningfully from TXA may provide justification for universal application. To date, the reported safety data in both TJA and other patients have been reassuring and, importantly, do not point to a risk of excess harm from TXA either generally or in any identifiable subgroup. Although future such data might dissuade the practice of universal TXA administration, continued absence of evidence of harm would focus decision making on comparisons of efficacy between patients with differing risk for transfusion.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…TXA has also been exonerated from causing venous thromboembolism (VTE). A recently published meta-analysis concluded that administration of topical, IV, and oral TXA was not associated with an increased risk of VTE [33]. We also found no differences between both groups in terms of DVT, pulmonary embolism, and 90-day readmissions.…”
Section: Discussionsupporting
confidence: 58%
“…These variables are also predisposing factors for increased PJI. Based on recent studies on the safety of TXA, the indications for TXA are increasing even in sicker patients [33,35,45,46]. In an effort to remove the influence of these variables, we did perform a regression analysis to identify the influence of TXA administration alone on the incidence of PJI.…”
Section: Discussionmentioning
confidence: 99%